Mycobacterium chelonae causing chronic wound infection and abdominal incisional hernia - Susan Verghese; Parag Agrawal; Santosh Benjamin (Indian Journal of Pathology and Microbiology, 2014)
Mycobacterium chelonae is a rapidly growing mycobacterium that is found all over the environment, including sewage and tap water. They are important species associated with chronic non-healing wounds. We report a case in a 41 year old female patient who underwent multiple surgeries for an ovarian cyst, tubo-ovarian abscesses with peritonitis and a repair of an abdominal incisional hernia.